(untitled) - Ratner, Peter (New York,[Chichester], 2003)
This Second Edition combines detailed, practical information about creating and animating 3-D human models. More than 400 images, interactive files, and exciting animations included on the CD-ROM detail the modeling and animation processes for both male and female figures. Chapter objectives and exercises are tied to the CD-ROM, which also provides color example images, sample models, modeling templates, textures, lesson plans, and relevant animation movies that allow you to start modeling and animating right away!
Keywords: Computer animation,Computer simulation,Human figure in art,Hoạt hình máy tính,Bộ mô phỏng máy tính,Nhân vật trong mỹ thuật